Minimum Inhibitory Concentration of Iron Oxide Nanoparticles with Hydrogen Peroxide against Endodontic Enterococcus faecalis - Saraa N. Al-Mallah; Ali M. Al-Naimi (University of Mosul, College of Dentistry, 2021)
Aims: This study aimed to assess the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) effect of iron oxide nanoparticles (IONPs) in combination with hydrogen peroxide (H2O2) by evaluating its effect against endodontic Enterococcus Faecalis (E. faecalis) in the planktonic model. Materials and Methods: the tested irrigants groups (IONPs, 3% H2O2, 5.25% NaOCl, IONPs+H2O2) were serially diluted in brain heart infusion broth, and 100 μl of standard microbial suspensions of E. faecalis were added. The results were obtained based on turbidity and growth on selective enterococcus agar plates. Result: IONPs+H2O2 showed to be more effective against E. faecalis than IONPs, 3% H2O2 and 5.25% NaOCl as lower dilutions were required to inhibit the growth of the bacteria. NaOCl exhibited an antibacterial effect equivalent to that of H2O2, while IONPs exhibited a stimulatory growth at the high tested concentration. Conclusions: IONPs+H2O2 showing promissory antibacterial properties as an intracanal irrigating solution to control E. faecalis from the infected root canal.